The reliability improvement in irrigation services: application of rotational water distribution to tertiary canals in Central Asia - Abdullaev, Iskandar; Ul-Hassan, Mehmood; Manthrithilake, Herath; Yakubov, Murat (International Water Management Institute, 2006)
This report addresses a specific context of massive inequity and unevenness in water allocation and distribution experienced presently by the water users in transitional Central Asian economies, as a result of broad-scale fragmentation of the previously large farms. The report describes action research aimed at making water distribution at the tertiary level more reliable, transparent and equitable.